Pengaruh Model Pembelajaran Cooperative Learning Tipe Jigsaw Terhadap Hasil Belajar Siswa Di SMA Negeri 6 Halmahera Utara - Yosina Sylena Souhuwat; Septiany Ch Palilingan (Oxygenius Journal Of Chemistry Education, 2022)
The purpose of this study was to determine the difference in the average student learning outcomes of classes taught with the jigsaw cooperative learning model and the average learning outcomes of conventional models. This research is a quantitative study using a non-equivalent control group design. The population in this study were all students of class XI MIPA SMA Negeri 6 North Halmahera, the sample consisted of 2 classes, namely XI MIPA 3 as the control class and XI MIPA 4 as the experimental class. Research data obtained in the form of the difference in the average value of the pretest and posttest, the experimental class of 29.7, and the difference in the average value of the pretest and posttest of the control class of 17.95. After being tested through the t-test, the results obtained between the control class and the experimental class were significant, namely = 2,024 Thus, it can be concluded that there is a difference in the average learning outcomes of classes that are applied using the jigsaw type of cooperative learning model with classes that use conventional models.